A United States Fair Lending Perspective on Machine Learning - Hall, Patrick; Cox, Benjamin; Dickerson, Steven; Ravi Kannan, Arjun; Kulkarni, Raghu; Schmidt, Nicholas (Frontiers in Artificial Intelligence, 2021)
The use of machine learning (ML) has become more widespread in many areas of consumer financial services, including credit underwriting and pricing of loans. ML’s ability to automatically learn nonlinearities and interactions in training data is perceived to facilitate faster and more accurate credit decisions, and ML is now a viable challenger to traditional credit modeling methodologies. In this mini review, we further the discussion of ML in consumer finance by proposing uniform definitions of key ML and legal concepts related to discrimination and interpretability. We use the U.S. legal and regulatory environment as a foundation to add critical context to the broader discussion of relevant, substantial, and novel ML methodologies in credit underwriting, and we review numerous strategies to mitigate the many potential adverse implications of ML in consumer finance.